2022
DOI: 10.3389/fendo.2022.963191
|View full text |Cite|
|
Sign up to set email alerts
|

The possible correlation between serum GRB2 levels and carotid atherosclerosis in patients with type 2 diabetes mellitus

Abstract: Background and purposeGrowth factor receptor-bound protein 2(GRB2), a bridging protein. An animal study showed that downregulation of GRB2 inhibited the activation of PI3K/AKT/NF-kB pathway which improved lipid accumulation and inflammatory infiltration in rats with atherosclerosis (AS), resulting in an anti-AS effect. This was the first study to investigate blood GRB2 levels in type 2 diabetes mellitus(T2DM) patients with carotid atherosclerosis (CAS), exploring its relationship with various metabolic indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Proctor et al (2007) demonstrated the necessity of GRB2 for atherosclerotic lesion formation through oxidized LDL uptake by macrophages in a mice model [31]. Similarly, Dong et al (2022) found increased serum GRB2 concentrations in individuals with both T2DM and carotid atherosclerosis (CAS) [32]. Also, they observed a linear correlation between the serum GRB2 level and carotid intima-media thickness, indicating the potential involvement of GRB2 in the development of T2DM with CAS [32].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Proctor et al (2007) demonstrated the necessity of GRB2 for atherosclerotic lesion formation through oxidized LDL uptake by macrophages in a mice model [31]. Similarly, Dong et al (2022) found increased serum GRB2 concentrations in individuals with both T2DM and carotid atherosclerosis (CAS) [32]. Also, they observed a linear correlation between the serum GRB2 level and carotid intima-media thickness, indicating the potential involvement of GRB2 in the development of T2DM with CAS [32].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Dong et al (2022) found increased serum GRB2 concentrations in individuals with both T2DM and carotid atherosclerosis (CAS) [32]. Also, they observed a linear correlation between the serum GRB2 level and carotid intima-media thickness, indicating the potential involvement of GRB2 in the development of T2DM with CAS [32]. Additionally, Wang et al (2021) established the link between cardiorenal syndrome type 3 (CRS-3) and elevated IL-6/GRB2, which plays an important role in cardiac dysfunction by suppressing the Akt/mTOR signaling pathway and inducing impairment in cardiomyocyte mitochondrial bioenergetics [33].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Foreign language retrieval was conducted in Pubmed using Diabetes/T2DM, Extremities,Lower Extremities and RiskFactors as search terms.With the subject words "Type 2 diabetes mellitus, carotid plaque formation AND risk factors" as the main search terms, the combination of subject words AND free words was adopted, and finally "(type 2 diabetes ORT2DM) AND (related factors OR risk factors ISSN 2618-1584 Vol. 5…”
Section: Literature Retrieval Strategymentioning
confidence: 99%
“…The 32 literatures included were case-control studies, published between 2003 and 2023, with a total of 5710 cases in the case group and 5405 cases in the control group. (Table 1) Dong Xia [5] 2021 Hebei Case control 105 50 (6) 7 2…”
Section: Basic Features Of Literature Inclusion and Quality Evaluationmentioning
confidence: 99%